Sexual Harassment Prevention Training on Personal Safety Skills of Special Needs Students - Risnida Muzdalifah; Muryantinah Mulyo Handayani (Fakultas Ilmu Pendidikan)
This study was conducted to get an overview of the effectiveness of prevention of sexual harassment training on personal safety skills of special needs students. The hypothesis proposed in this study is there is a role of prevention of sexual harassment training on the personal safety skills of special needs. Number of the subjects on this study are 10 people. Effectiveness of training was measured by learning evaluation and learning behavior tools. Learning evaluation was measured by student knowledge before and after training. Learning behavior was measured used checklist to see whether the action plan that has been made is implemented properly. The results showed that there was a role in providing training to prevent sexual harassment on personal safety skills of special needs students as indicated by a significance value of 0.011 <0.005; 0.006 <0.05; and 0.015 <0.05.